The Effect of the Think-Pair-Share Model Assisted by Animated PowerPoint on the Mathematical Representation Ability of Generation Alpha Students - Iramadhania, Fahira; Hasanah, Rusi Ulfa (Desimal: Jurnal Matematika, 2026)
Mathematical representation ability is an essential competency that enables students to represent, organize, and communicate mathematical ideas through visual, symbolic, and verbal forms. However, many students still experience difficulties in transforming mathematical problems into different forms of representation and explaining solution processes accurately, indicating that this competency remains insufficiently developed. Therefore, this study aimed to determine the effect and the magnitude of the effect of the Think-Pair-Share (TPS) learning model assisted by animated PowerPoint on the mathematical representation ability of Generation Alpha students in learning cubes and rectangular prisms. This study employed a quantitative approach using a quasi-experimental design with a Posttest-Only Control Group Design. The sample was selected through cluster random sampling, with Class VII-4 serving as the experimental group and Class VII-2 as the control group, each consisting of 31 students. Data were collected using a validated and reliable six-item open-ended mathematical representation test and were analyzed using descriptive and inferential statistics, including normality, homogeneity, t-test, and effect size analyses. The findings showed that the experimental group achieved a higher mean posttest score (82.890) than the control group (56.142). The t-test results indicated a t value of 7.559 with a significance value of 0.000 < 0.05, indicating a significant effect of the TPS model assisted by animated PowerPoint on students' mathematical representation ability. Furthermore, the effect size was 1.92, indicating a high effect. Therefore, the animated PowerPoint-assisted TPS model is effective in improving students' mathematical representation ability and can serve as an alternative instructional approach for mathematics learning.